Customary system as ‘constraint’ or ‘enabler’ to peri-urban land development: Case of Kisumu city, Kenya - Wamukaya, Edwin; Mbathi, Musyimi (Town and Regional Planning, 2019)
Scholarly research on land delivery processes and land tenure dynamics in the context of accelerated urbanization and massive rural-urban land use conversion in sub-Saharan African cities remains limited, especially in Kenya. Kisumu city, Kenya’s third largest urban agglomeration, is currently experiencing spontaneous growth and uncontrolled outward expansions of urban development from the urban centre. This is taking place in the peri-urban areas and rural hinterland, where urban-based actors, under the pressure and anticipation of urbanization, undertake land transactions, land tenure conversions, and land development. Making use of three case studies that represent contrasting phases of settlement formation (incipient, intermediate, and consolidated), this article attempts to provide knowledge, particularly on the relationship between the land delivery processes, land tenure dynamics, and the role of various actors involved in the context of land development. The results indicate that the current trend with regard to landholding in the case study areas was a gradual shift from community control to individualisation. There is a need to integrate both customary and public authority’s efforts towards orderly urban development. This study thus advocates for partnerships between the municipal authority and neocustomary/customary actors and, where appropriate, uses their creativity in solving problems to adapt municipal by-laws and procedures.